BOOK REVIEW LAW AND POLITICS OF CONSTITUTIONAL COURTS - Simmons, Thomas E. (UI Scholars Hub, 2018)
Stefanus Hendrianto’s “Law and Politics of Constitutional Courts” is part of Routledge’s series titled “Comparative Constitutionalism in Muslim Majority States.” The book combines several narratives and themes. It summarizes the late 20th century political history of Indonesia. It describes the birth of the Indonesian Constitutional Court. It advances the idea of judges as prudential-minimalist heroes. It considers Aristotle and the scholarship of Mark Tushnet. It presents weird analogies to the IIliad, the Odyssey, and the heroic tales contained the epic Mahabharara. But primarily it is an extended legal biography of the Constitutional Court’s founding chief justice, Jimly Asshibbiqie. In a kind of extended epilogue, the book examines the impact of Justice Asshibbique’s successor, Chief Justice Mohammad Mahfud, as well as the legacy of the third-generation court from 2013 to present day.